2022
DOI: 10.5498/wjp.v12.i1.59
|View full text |Cite
|
Sign up to set email alerts
|

Depression among caregivers of patients with dementia: Associative factors and management approaches

Abstract: As elderly people increasingly come to represent a higher proportion of the world’s population, various forms of dementia are becoming a significant chronic disease burden. The World Health Organization emphasizes dementia care as a public health priority and calls for more support for family caregivers who commonly play a significant, central role in dementia care. Taking care of someone with dementia is a long-term responsibility that can be stressful and may lead to depression among family caregivers. Depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 116 publications
(104 reference statements)
2
17
1
Order By: Relevance
“…The caregiver-patient relationship was identified to have a significant association with depressive symptoms in caregivers of PwD, where non-spousal caregivers suffered from significantly greater depressive symptoms than spousal caregivers. This finding contrasts with previous studies which found that spousal relationships were associated with greater depressive symptoms, strain, and psychological morbidity [8,54,134,153]. This could be explained by the age of the caregivers in our study as more than 90% of the non-spousal caregivers were children, children-in-law, and grandchildren.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The caregiver-patient relationship was identified to have a significant association with depressive symptoms in caregivers of PwD, where non-spousal caregivers suffered from significantly greater depressive symptoms than spousal caregivers. This finding contrasts with previous studies which found that spousal relationships were associated with greater depressive symptoms, strain, and psychological morbidity [8,54,134,153]. This could be explained by the age of the caregivers in our study as more than 90% of the non-spousal caregivers were children, children-in-law, and grandchildren.…”
Section: Discussioncontrasting
confidence: 99%
“…At the bivariate level, the first factor related to depressive symptoms among the caregivers of PwD was the patient's age, where caregivers of younger PwD experience a higher level of depressive symptoms. This finding was consistent with those of previous studies [30,54,133,134]. Malaysia has an aging population, where its transition from aging to and aged society in just 24 years has followed the trend in other countries with highincome economies, e.g., Japan.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this meta‐analysis, seven studies had an intervention duration of ≥8 weeks, and three of the studies showed a significant reduction in depression (Danucalov et al., 2013; Kor et al., 2022; Whitebird et al., 2013). Caregivers of persons living with dementia frequently suffer depression as a result of the complex and difficult duty of caring for persons living with dementia without knowing when this caregiving will end (Cheng et al., 2021; Huang, 2022). As a result, a more appropriate strategy than mindfulness‐based interventions such as cognitive‐behavioral therapy and interpersonal therapy aimed at improving dysfunctional thoughts and increasing gratifying activities is necessary to assist caregivers in coping with stressful and difficult situations (Biliunaite et al., 2021; Bruijniks et al., 2022; Whiston et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reduction of activities of daily living may result in a greater level of care that consequently increases caregiver’s stress. Caregiver depression is thought to be a consequence of care due to a complex interplay of factors that comprises dimensions of the patient, caregiver, and cultural background [ 26 ]. It is important to note that a potential increase in suicidal behavior is associated with all caregivers and not just caregivers of those with dementia.…”
Section: Discussionmentioning
confidence: 99%